PERAN PENGAMBILAN KEPUTUSAN DALAM MENINGKATKAN KINERJA SEKOLAH DI SMPN 2 KEPAHIANG - Revi Adekamisti; Dedi Candira W.K; Murni Yanto; Muhammad Istan; Beni Azwar (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to analyze the role of decision-making in improving school performance, focusing on a case study at SMP Negeri 2 Kepahiang. In the context of educational management, participatory decision-making processes are considered capable of creating a conducive school climate and encouraging student achievement. This research employs a qualitative approach with a case study method. The research subjects include the principal, teachers, administrative staff, and the school committee. Data were collected through in-depth interviews, direct observations in the school environment, and documentation studies of policies and programs implemented. The findings indicate that the involvement of all school elements in decision-making has a positive impact on school performance, particularly in academic achievement, student discipline, and parental satisfaction. Various programs such as teacher training, strengthened counseling services, and improved learning facilities have proven to enhance the quality of education. Additionally, support from the school committee and parents has increased significantly when they are actively involved in strategic decision-making processes. These findings highlight the importance of collaboration and transparency in school management to achieve educational goals more effectively.